THE EFFECT OF GOOD CORPORATE GOVERNANCE ON EMPLOYEE PERFORMANCE AT BPJS KETENAGKERJAAN SEMARANG - Agina, Afifah; Widyarti, Maria Theresia Heni; Widiarto, Ardian (Politeknik Negeri Semarang, 2024)
This study aims to determine the effect of good corporate governance on employee performance at BPJS Ketenagakerjaan Semarang. This research uses a quantitative approach. The population of this study were employees of BPJS Ketenagakerjaan Semarang. Data collection techniques were conducted by interview, questionnaire, and observation. The data analysis used in this research is multiple regression analysis with the help of SPSS version 22. The results of this study indicate that the principles of Transparency, Independency, Accountability, and Fairness have no effect on employee performance. While the principle of Responsibility affects employee performance. Based on the test results simultaneously the five principles of Good Corporate Governance affect employee performance.